Multi-wavelength brillouin fiber laser bragg grating - Amira Zakiah Malek (School of Microelectronic Engineering, Universiti Malaysia Perlis, 2017)
The main purpose of this research is to design and develop a fiber laser system operating in the C-band wavelength region that utilizes SBS and FBG effect. Specific objectives of this project are listed as follow ; to design and develop a simple configuration with low cavity loss of the MWBFL system by utilizing FBG ; to improve the BS signal quality in terms of number BS signal and OSNR value ; to analyze the Brillouin threshold power for first BS signal, numberBS signal, OSNR value and tuning range.